2012
DOI: 10.3892/ijmm.2012.1193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and differential expression of DRK1 in Sporothrix schenckii

Abstract: The dimorphism of Sporothrix schenckii (S. schenckii) reflects a developmental switch in morphology and lifestyle that is necessary for virulence. DRK1, a hybrid histidine kinase, functions as a global regulator of dimorphism and virulence in Blastomyces dermatitidis (B. dermatitidis) and Histoplasma capsulatum (H. capsulatum). The partial cDNA sequence of DRK1 of S. schenckii, designated SsDRK1, was obtained using degenerate primers based on the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…In S. schenckii, few studies have been conducted to identify key genes involved in triggering and maintaining the dimorphic changes. One gene (DRK1), encoding a hybrid histidine kinase (HHK), has been described as a master regulator of the hyphae-to-yeast transition and virulence in several dimorphic fungi, including S. schenckii [56,57]. The expression of this gene was reported to be up-regulated in the yeast-phase compared to the mould-phase [56,57] but, in our study, we found it (ORF Spsc_00605) to be not differentially expressed between mould and yeast forms of S. schenckii (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…In S. schenckii, few studies have been conducted to identify key genes involved in triggering and maintaining the dimorphic changes. One gene (DRK1), encoding a hybrid histidine kinase (HHK), has been described as a master regulator of the hyphae-to-yeast transition and virulence in several dimorphic fungi, including S. schenckii [56,57]. The expression of this gene was reported to be up-regulated in the yeast-phase compared to the mould-phase [56,57] but, in our study, we found it (ORF Spsc_00605) to be not differentially expressed between mould and yeast forms of S. schenckii (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…DRK1 is conserved in the dimorphic fungi with homologs identified in Sporothrix schenckii and Penicillium marneffei. 57,58 DRK1 transcript is 24-fold more abundant in S. schenckii yeast than hyphae. 57 In P. marneffei, the DRK1 homolog, DRKA, is important for germinating conidia to develop into the pathogenic yeast within macrophages at 37°C.…”
Section: Pathogenesis Overviewmentioning
confidence: 97%
“…57,58 DRK1 transcript is 24-fold more abundant in S. schenckii yeast than hyphae. 57 In P. marneffei, the DRK1 homolog, DRKA, is important for germinating conidia to develop into the pathogenic yeast within macrophages at 37°C. 58 Over the past decade, there has been increasing interest in understanding the yeast-to-hyphal transition following a drop in temperature from 37 to 22-25°C.…”
Section: Pathogenesis Overviewmentioning
confidence: 97%
“…Genes such as histidine kinase ( drk1 ) regulates the transition of mycelium to yeast and consequently the maintenance of virulence in B. dermatitidis and H. capsulatum [16]. This gene, also identified in S. schenckii, shows 65% of identity with its ortholog in B.dermatitidis and seems to be highly expressed during the yeast stage [17]. …”
Section: Introductionmentioning
confidence: 99%